On the Efficiency and Stability of a Two-Way Flow Network with Small Decay: A Note - Charoensook, Banchongsan (Estudios de Economía, 2025)
The seminal two-way flow strategic network formation model of Bala and Goyal (2000b) exhibits a substantial tension between stability and efficiency. In this note, I show that despite this tension every link receiver in a Nash network serves as an efficient transmitter of information assuming a small degree of information decay. Thus, a strategic decision of every link sender, who always forms links with efficient link receivers for his own interest, does in part lead to a socially desirable outcome. I also show how this finding can potentially refine some results in the literature.